Africa, the new billionaire continent - (:unkn) unknown (My University, 2010)
[The traditional division of the world into five continents leads to oppose Asia, where lives 60% of the world's population, and the very low population of Oceania. Between these extremes, the respective position in Europe, America and Africa evolves. According to estimates, Africa has surpassed the billion people on the edge of the 2010s.]
Keywords: African Research